Effect of Computer-Assisted Cognitive Training on Visual Perception in Children with Intellectual Development Disorders - LI Zhaoying; DENG Haiyin; HUANG Zhenming; HE Youze; TU Jingnan; CAO Lei; HUANG Jia; WU Jingsong (康复学报)
ObjectiveTo explore the clinical rehabilitation effect of a computer-assisted cognitive training on visual perception function of children with intellectual development disorders (IDD).MethodsA total of sixty IDD participants, aged 4-6.5 years old, recruited from special education schools and children's rehabilitation centers in Fuzhou city between August 2019 to December 2020, were included in the study, and they were randomly divided into control group and experimental group, with 30 cases in each group, 4 cases dropped out during the process of the study in each of the two groups. The control group was trained with manual cognitive training, and the experimental group was trained with the computer-assisted cognitive training, five times per week for five weeks. The outcomes measures included the scores of visual perception test (VPT) in Beery-Buktenica developmental test of visual-motor integration sixth edition (VMI-6), Peabody picture vocabulary test (PPVT), and parent symptom questionnaire (PSQ). Scores were compared at baseline, post-intervention and 3-month follow-up. The intention-to-treat principle was applied in the statistical analysis. Then, the mixed linear model analysis was used to explore the group effect, time effect and interaction effect of intervention with the chronological age and body mass index of the subjects as covariates.ResultsThere was no statistically significant difference found in the scores of each index at baseline between the two groups (P>0.05). The results of mixed linear model analysis showed a significant group × time interaction effect of computer-assisted cognitive training on VPT and PPVT (P<0.05). The results of the between-group comparison showed that the experimental group was better than the control group in terms of improvement in VPT [d=0.56, 95% CI (0.05, 1.08)] and PPVT [d=0.20, 95% CI (-0.30, 0.71)] (P<0.01) before and after treatment. Compared with the baseline, the results of the between-group comparison in the follow-up period showed that the improvement effects of VPT [d=0.80, 95% CI (0.27, 1.32)], PPVT [d=0.79, 95% CI (0.27, 1.32)], and PSQ learning problems [d=-0.11, 95% CI (-0.62, 0.40)] in the experimental group were significantly superior to those in the control group (P<0.01).ConclusionThe five-week computer-assisted cognitive training can be effective in improving visual-perceptual functioning in children with IDD, and also promote improvements in vocabulary, learning problems, and attentional behaviors.